Self-inflicted laser-induced maculopathy in adolescence - Hohberger, B.; Bergua, A. (Ophthalmologe, 2016)
Reports of laser-induced ocular injuries have become more frequent in recent years, especially due to high-energy laser pointers. The article presents for the first time in the German literature a case of self-inflicted laser-induced maculopathy in an adolescent. In addition to the clinical findings, the results of funduscopy and spectral domain optical coherence tomography (SD-OCT) follow-up are presented.
EVALuna2:21314